Wind Chamber Music by Women Composers - The Biographies, Compositional Techniques, and Perspectives of Jocelyn Morlock, Elizabeth Raum, Marilyn Shrude, and Augusta Read Thomas - Stahl, Shayna (My University, 2019)
The purpose of this dissertation is to explore the perspectives of four women composers to address the need for visibility of women composers and their wind chamber music. Interviews with Jocelyn Morlock, Elizabeth Raum, Marilyn Shrude, and Augusta Read Thomas will provide insight into their lives as composers, information about their compositional processes and styles, their wind chamber compositions, and perspectives on what it means to be a composer today. The overall goal is to elevate wind chamber music written by women composers in the world of art music. The themes that emerged from the composer interviews highlight the continued need to research and promote women composers and their wind chamber music. The dissertation addresses concerns such as motherhood and family, perceived barriers faced by women, the #MeToo movement, and bullying in academia. It also presents advice from the individuals interviewed for women composers on work ethic, perseverance, and networking. It is the author’s goal to provide a resource to help increase awareness of wind chamber works written by women composers. A compendium of 1,188 wind chamber works written by 291 women composers, consisting of four or more wind instruments is available as a direct result of this research. All wind chamber compositions found for this study will be listed online and in Appendix D.
Thesis (D.M.A.)--University of Washington, 2019
Keywords: Augusta Read Thomas; Elizabeth Raum; Jocelyn Morlock; Marilyn Shrude; Wind Chamber Music; Women Composers; Music; Music